Hepatoprotective Effect of Hepatophyt in Experimental Drug Hepatitis - S. M. Nikolaev; Z. G. Sambueva; YA. G. Razuvaeva; A. O. Zandanov; L. E. Markhaeva (Антибиотики и Химиотерапия, 2020)
The hepatoprotective action of Hepatophyt was studied on Wistar rats with experimental hepatitis caused by exposure of the animals to tetracycline. Hepatophyt was administered per os in a dose of 0.1 g/kg. Its significant pharmacotherapeutic action was due to the content of biologically active substances, mainly of polyphenol nature. As natural antioxidants, they provided stabilization of the biomembranes and increased the energetic potential of the hepatic cells and the contractile capacity of the pericanal microfilaments, thus stimulating the synthesis and transport of the cholates and excretion of bilirubin and cholesterol with bile.